Meta-Analysis of VTE Risk: Ovarian Cancer Patients by Stage, Histology, Cytoreduction, and Ascites at Diagnosis - Kristin S. Weeks; Emma Herbach; Megan McDonald; Mary Charlton; Marin L. Schweizer (Obstetrics and Gynecology International)
Venous thromboembolisms (VTEs) have been a leading secondary cause of death among ovarian cancer patients, prompting multiple studies of risk factors. The objective of this meta-analysis is to quantify the associations between VTE and the most commonly reported risk factors among ovarian cancer patients. PubMed, Embase, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were used to identify observational studies. Two reviewers independently abstracted data and assessed quality via the Newcastle–Ottawa tool. A random effects model was used to calculate the pooled odds ratios for VTE with each of the following exposures: advanced cancer stage, clear cell histology, serous histology, ascites at diagnosis, and complete cytoreduction. The I2 and Q tests were used to evaluate heterogeneity. Twenty cohort studies with 6,324 total ovarian cancer patients, 769 of whom experienced a VTE, were included. The odds of VTE in ovarian cancer patients were higher among patients with cancer stage III/IV (versus cancer stage I/II, pooled odds ratio (OR) 2.73; 95% CI 1.84–4.06; I2= 64%), clear cell (versus nonclear cell) histology (OR 2.11; 95% CI 1.55–2.89; I2 = 6%), and ascites (versus no ascites) at diagnosis (OR 2.12; 95% CI 1.51–2.96; I2 = 32%). Serous (versus nonserous) histology (OR 1.26; 95% CI 0.91–1.75; I2 = 42%) and complete (versus incomplete) cytoreduction (OR 1.05; 95% CI 0.27–4.11; I2 = 88%) were not associated with VTE. This meta-analysis quantifies the significantly elevated odds of VTE in ovarian cancer patients with advanced stage at diagnosis, clear cell histology, and ascites at diagnosis. Further studies are needed to account for confounders and inform clinical decision-making tools.